Proyecto de plan de desarrollo de un local de diversión “sports zone bar - Paredes Fajardo, Verónica (2010)
In the actuality, there are small the Public Laboratories of Latin America that have had the possibility of being producers of vaccines of human use recognized by the quality and under cost of the same. Nevertheless the National Institute of Hygiene is among the producers of some vaccines used in the different programs of immunization worldwide, by what there is generated an opportunity of that it should be taken advantage to start exporting; for this they will have to do certain investments for that they can be competitive on the market. The Objective country initially would be Bolivia; this country in the last years has been investing in the area of health due that in last decades it was registering extremely high information of the rates of mortality in five-yearold minors. From 1997 confronts the challenge of reducing these rates demonstrating the interest that is had in this area. The principal reasons of the deaths of the children minors owe to diseases that could be prevenibles for the use of vaccines across the extended programs of immunization.